Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1002/chin.198829125
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Phenyl‐α,α,ω‐trihydropolyfluoroalkyliodonium Borofluorides.

Abstract: ChemInform Abstract In the presence of BF3 the reaction between the difluoroiodotrihydropolyfluoroalkanes (I) and benzene (II) affords the title compounds (III). Their perfluoro analogues are known to be strong perfluoroalkylating agents. For a comparison, the alkylating properties of the title compounds (III) with a methylene bridge between the aryliodonium moiety and the polyfluoroalkyl group are investigated. In the reaction of (IIIa) with p-chlorothiophenol (IV) the perfluoroalkyl group adds to the sulfur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…61 In contrast to FMITS (Table 12, run 3) which produced only the N-polyfluoroalkylated product 129 (R f ′ ) CF 3 ), the tetrafluoroborate reagent 127 produced both N-and C-polyfluoroalkylated products 129 and 130 (R f ′ ) (CF 2 CF 2 ) 2 H) (eq 39). 61 The dependence of the products' identities on the counteranins -OTf and BF 4is noteworthy. However, FITS did produce a small amount of the C-dihydroperfluoroalkylated product in addition to the O-dihydroperfluoroalkylated prod-uct when reacted with lithiun salts of more active phenol derivatives.…”
Section: (Polyfluoroalkyl)aryliodonium Salts and (Dihydroperfluoroalk...mentioning
confidence: 99%
See 2 more Smart Citations
“…61 In contrast to FMITS (Table 12, run 3) which produced only the N-polyfluoroalkylated product 129 (R f ′ ) CF 3 ), the tetrafluoroborate reagent 127 produced both N-and C-polyfluoroalkylated products 129 and 130 (R f ′ ) (CF 2 CF 2 ) 2 H) (eq 39). 61 The dependence of the products' identities on the counteranins -OTf and BF 4is noteworthy. However, FITS did produce a small amount of the C-dihydroperfluoroalkylated product in addition to the O-dihydroperfluoroalkylated prod-uct when reacted with lithiun salts of more active phenol derivatives.…”
Section: (Polyfluoroalkyl)aryliodonium Salts and (Dihydroperfluoroalk...mentioning
confidence: 99%
“…In contrast to (2,2,2trifluoroethyl)phenyliodonium triflate (FMITS-1) which was synthesized in high yield, 57 (2,2,2-trifluoroethyl)phenyliodonium tetrafluoroborate could not be synthesized by the same method as 127 and 128. 61 (1,1,3-Trihydrotetrafluoropropyl)phenyliodonium tetrafluoroborate could not be synthesized. 61 The FITS and FMITS reagents were compared by thermolysis.…”
Section: (Polyfluoroalkyl)aryliodonium Salts and (Dihydroperfluoroalk...mentioning
confidence: 99%
See 1 more Smart Citation
“…They failed in synthesizing (2,2,2-trifluoroethyl)phenyliodonium tetrafluoroborate [38]. Unfortunately, we failed to synthesize the trifluoromethyl analog (FITS-1) because of the abnormality of CF 3 group.…”
Section: (Perfluoroalkyl)phenyliodonium Trifluoromethanesulfonates Anmentioning
confidence: 90%
“…Yagupolskii et al [38] reported the synthesis of (a, a, vtrihydroperfluoroalkyl)phenyliodonium tetrafluoroborates and a, a, v-trihydroperfluoroalkylation of some substrates with them.…”
Section: (Perfluoroalkyl)phenyliodonium Trifluoromethanesulfonates Anmentioning
confidence: 98%